Dampak Pernikahan Dini yang Berhubungan dengan Kesehatan Reproduksi pada Remaja Putri - Gusmawati Gusmawati; Fera Murwita; Marniati Marniati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Early marriage in Indonesia is a significant reproductive health issue, particularly for adolescent girls. This study aims to explore the impact of early marriage on reproductive health and the contributing factors. Early marriage, defined as marriage before the age of 19, can lead to various health problems, including a high risk of pregnancy complications and mental health issues. Data indicates that Indonesia has a high rate of early marriage, with the highest prevalence in several provinces. The method used is a literature review analyzing 30 relevant scientific journals from 2015 to 2025. The findings indicate that early marriage is associated with an increased risk of pregnancy complications, disturbed mental health, and low knowledge about reproductive health among adolescent girls. Further efforts are needed in reproductive health education and policies to prevent early marriage.